From Tweets to Trust: A Theoretical Review on Social Media Sentiment, Corporate Legitimacy, and Financial Outcomes - Kusuma, Yuni Kusuma Arumsari; Soekarno, Oddi Soekarno Putra; Abo, Nekad Samudra (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This paper provides a theoretical review exploring the effect of social media sentiment on corporate legitimacy and financial performance, integrating knowledge from CSR communication, digital reputation, and market response literature. This topic is critical as digital platforms now dominate reputation management. Background Problems: Although social media heavily influences CSR and reputation, the mechanism by which positive and negative social sentiment affects a firm’s legitimacy and financial success remains poorly understood. This study addresses the central question: How do legitimacy processes, governed by digital stakeholder sentiment, operate within the corporate system? Research Methods: The research employs a narrative and thematic review of 100 peer-reviewed articles indexed in Scopus over the past ten years. This evidence is framed by Stakeholder Theory and Legitimacy Theory and grounded in empirical studies utilizing sentiment analysis, topic modelling, and machine-learning-based text analytics on social media data. Finding/Results: The review demonstrates that positive CSR/sustainability sentiment significantly enables corporate legitimacy, stakeholder trust, and financial indicators (stock prices/sales). Conversely, negative sentiment (particularly during crises) accelerates legitimacy loss and drops in valuation, an effect often moderated by established corporate reputation and industry context. Conclusion: We conclude that real-time sentiment observance is crucial for effective CSR communication strategies, ensuring their contribution to corporate legitimacy and financial performance in the digital age. Future research should combine multimodal data and influencer dynamics to build predictive models of legitimacy crises.